System Performance, Healthcare Workers’ Behavior, and Electronic Medical Record Completeness - Raden Suwargo; Sentot Imam Suprapto; Agusta Dian Ellina (Innovative Approaches in Health Science Journal, 2026)
Background: Incomplete electronic medical record (EMR) documentation may compromise clinical communication, administrative processes, and data quality. Evidence from Indonesian hospitals remains limited regarding the joint association of system-related and user-behavior factors with documentation completeness. Objective: To examine the associations of system performance and healthcare workers’ behavior with EMR completeness at Toeloengredjo Hospital, Kediri. Methods: This cross-sectional study included 132 of 196 inpatient healthcare workers selected through proportional random sampling. System performance, healthcare workers’ behavior, and EMR completeness were assessed using the study instruments. Pearson correlation examined bivariate associations, and multiple linear regression evaluated the independent and joint associations of the two predictors with EMR completeness. Results: System performance was positively correlated with EMR completeness (r = 0.434, p < 0.001), as was healthcare workers’ behavior (r = 0.375, p < 0.001). In the regression model, system performance (standardized β = 0.240, p = 0.023) and healthcare workers’ behavior (standardized β = 0.266, p = 0.012) were independently associated with EMR completeness. The model was statistically significant, F(2, 129) = 17.505, p < 0.001, with R² = 0.213 and adjusted R² = 0.201. Conclusion: Higher system-performance and healthcare-worker-behavior scores were associated with greater EMR completeness. The slightly larger standardized coefficient for healthcare workers’ behavior indicates a stronger adjusted association within this model, but the cross-sectional design does not establish causality.